INTRODUCTION OF LORA COMMUNICATION SYSTEM AND REMOTE CONTROL SYSTEM IN AGRICULTURAL AUTOMATION WITH INTERNET OF THINGS - Yani Prabowo; Jan Everhard Riwurohi; Wiwin Windihastuti; Fuad Hasan (Journal of Computer Science Advancements, 2025)
This research focuses on the integration of LoRa (Long Range) communication system and remote control system in agricultural automation with Internet of Things (IoT) using ESP32 microcontroller, Arduino nano and STM32 aims to improve the efficiency of intelligent agricultural management. LoRa is used as a long-range wireless communication protocol to collect data from sensors that are widely distributed in agricultural land, such as soil moisture sensors, temperature. The ESP32 microcontroller functions as the main controller that processes data from sensors and sends it in real-time to the control center via the LoRa network. Modbus is used as a standard serial communication protocol to connect sensors, actuators and other devices, thus ensuring compatibility between devices. In addition, Node-RED is used as a graphical interface (GUI) to manage data flow, control automation processes, and provide real-time data visualization to users. The results of this research are a stable integration system between sensor systems and communication systems. The novelty of this research is the integration of LoRa, ESP32, Modbus, and Node-RED to create a reliable and efficient agricultural automation system, enabling remote management of irrigation, fertilization, and environmental monitoring, thereby increasing agricultural productivity and optimizing resource use.